2017
DOI: 10.1007/s10461-017-1924-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalent Herpes Simplex Virus-2 Increases the Risk of Incident Bacterial Vaginosis in Women from South Africa

Abstract: Studies have shown that women diagnosed with herpes simplex virus-2 (HSV-2) have a higher risk for bacterial vaginosis (BV) infection. We investigated the presence of HSV-2 infections as a risk factor for incident BV infections in high risk, Human immunodeficiency virus (HIV) uninfected women enrolled in a HIV prevention trial in Durban, South Africa. The Vaginal and Oral Interventions to Control the Epidemic trial was a multicentre, double blinded, randomized controlled trial which was designed to estimate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…A recent study revealed that antibiotic-induced VD in mice resulted in a fall of antiviral protection against HSV-2 infection [115]. Furthermore, the association between BV and HSV-2 has also been confirmed in a recent study in South Africa with a large (n = 2750) cohort of patients [116]. In this study, women who had an HSV-2 infection at enrolment were shown to be at increased risk for incident BV infections and, certain risk factors like young age, unmarried and having a partner that has other partners, were significantly related with subsequent BV.…”
Section: Bacterial Vaginosis and Sexually Transmitted Diseases (Stds)mentioning
confidence: 72%
“…A recent study revealed that antibiotic-induced VD in mice resulted in a fall of antiviral protection against HSV-2 infection [115]. Furthermore, the association between BV and HSV-2 has also been confirmed in a recent study in South Africa with a large (n = 2750) cohort of patients [116]. In this study, women who had an HSV-2 infection at enrolment were shown to be at increased risk for incident BV infections and, certain risk factors like young age, unmarried and having a partner that has other partners, were significantly related with subsequent BV.…”
Section: Bacterial Vaginosis and Sexually Transmitted Diseases (Stds)mentioning
confidence: 72%
“…Many of these factors have been shown to contribute to the prevalence of sexually acquired infections. 27,28,29,30 The emergence of macrolide resistance in M. genitalium has drawn recent attention. 18,20,21,22,23 The first study to report on macrolide resistance in M. genitalium in South Africa was conducted by Hay et al in the Limpopo province of rural South Africa in 2015.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this practice may be less likely to explain the differences found in our study. Finally, we did not have complete information on other STIs (eg, herpes simplex virus-2) that may affect the vaginal microenvironment and susceptibility to BV 30…”
Section: Discussionmentioning
confidence: 99%